Under the Bridge: Utilizing Covered Liminal Spaces for Sanctioned Homeless Encampments in the City of Seattle - Baker, Max (My University, 2016)
The number of homeless sleeping outside in Seattle has increased significantly in the past few years, from 2,600 in 2012 to 4,500 in 2016. In response, the City has begun to spearhead the development of temporary sanctioned homeless encampments on vacant public land as an innovative alternative to an overburdened emergency shelter system. Vacant land remains a valuable, limited commodity in the rapidly growing Puget Sound region, however, making it difficult for the city to want to remove developable land from its inventory, even if only temporarily. Thus, land beneath and adjacent to rights-of-way presents an option for the placement of homeless encampments that doesn’t utilize developable land. Numerous bridges, overpasses, and viaducts are employed in the city’s transportation system to overcome physical impediments such as rivers and steep slopes, creating voids or “liminal spaces” in the urban landscape beneath them. This thesis looks to expand upon the City of Seattle’s current site selection process for encampments by considering these covered liminal spaces as a viable option. The first section of this document covers the history and policies surrounding homelessness in the United States, while precedent studies examine different ways in which covered liminal spaces have been re-conceptualized as public assets that are either informal, formal, or prototypical in nature. The research study chapter describes the background research, GIS analysis, and field visits that were conducted during the site selection process. A scoring system was developed based upon a site’s access to transit, proximity to homeless service centers, and current use, with three sites being ultimately chosen for field visits. Design recommendations and vignettes are subsequently presented for each site. In the end, expansion of the City of Seattle’s encampment site-selection process to include covered liminal spaces offers up a significant amount of practicable underutilized land within the city for hosting the homeless while simultaneously improving otherwise discounted urban spaces.
Thesis (Master's)--University of Washington, 2016-06
Keywords: Encampment; Homeless; Liminal; Marginalized; Urban; Urban planning; Public policy; Public health